Tinjauan Teologis Ke-Bapa-an Allah dan Relevansinya terhadap Peran Ayah dalam Sistem Keluarga - Surya Leung (STT Iman Jakarta, 2020)
The biggest obstacle to the failure of the father to represent the Fatherhood of God is the fall of man into sin and the loss of the image of the perfect Father in man. Humans fail to follow His will, including in living out their fatherly role as a father. The Father provided His only begotten Son, Christ for fathers. Thus, only through Christ, the Father returns His perfect image to fathers. When a father exemplifies Christ’s relationship with His Father in heaven, he can represent the image of the Fatherhood of God to His children. Only through Christ, fathers can play their part in the family system according to the will of their Father in heaven. This study uses an exposition method to several passages in the Bible that represent theological views of the Fatherhood of God towards His chosen people. This theological study is the basis for implementing paternity in Christian families today. AbstrakPenghalang terbesar kegagalan ayah merepresentasikan ke-Bapa-an Allah adalah kejatuhan manusia dalam dosa, dan hilangnya citra Bapa yang sempurna dalam diri manusia. Manusia gagal mengikuti kehendak-Nya termasuk dalam menghidupi peran ke-bapa-an mereka sebagai ayah. Bapa menyediakan Anak-Nya yang tunggal, yaitu Yesus Kristus, bagi para ayah, sehingga hanya melalui Kristus, Bapa mengembalikan citra-Nya yang sempurna bagi para ayah. Ketika seorang ayah yang meneladani relasi Kristus dengan Bapa-Nya di surga, ia dapat merepresentasikan citra ke-Bapa-an Allah kepada anak-Nya. Hanya melalui Kristus, ayah dapat menjalankan peranannya dalam sistem keluarga sesuai kehendak Bapa di surga. Penelitian ini menggunakan metode eksposisi terhadap beberapa bagian dalam Alkitab yang merepresentasikan pandangan teologis tentang ke-Bapa-an Allah kepada umat pilihan-Nya. Kajian teologis inilah yang menjadi dasar dalam mengimplementasikan ke-bapa-an ayah dalam keluarga Kristen masa kini.